Incentivized Payments in Experimental Games can Lead to Behavioural Change? - Bartels, Lara; Falk, Thomas; Vollan, Björn; Duche, Vishwambhar (2021)
Prepared by: Lara Bartels, Thomas Falk, Björn Vollan, Vishwambhar Duche